Perbandingan Tiga Metode Isolasi DNA Asperigilus niger - Donastin, Adyan; Koentjoro, Maharani Pertiwi; Hidayat, Muhamad Taufik; Prasetyo, Endry Nugroho (Metamorfosa: Journal of Biological Sciences, 2022)
Polymerase Chain Reaction (PCR) is a technique that is applied to detect and test the presence of genetic material from pathogenic fungi. This method was further developed because it has a high sensitivity compared to the culture method in detecting the presence of pathogenic fungi. To perform sensitive, specific and reliable PCR-based assays, the availability of pure DNA as well as an easy-to-perform DNA extraction protocol is essential. Currently, existing protocols for DNA extraction generally require specialized kits and with the addition of enzymes. Therefore, this study was conducted to compare the quantity and quality of Aspergillus niger DNA isolation with three different methods. The stages of the research carried out included pure A. niger culture and total DNA isolation using three methods, namely the protocol according to the Wizard® Genomic DNA Purification Kit (P1) instructions, Modified Wizard® Genomic DNA Purification Kit (P2) and Monarch Genomic DNA Purification Kit NEB (P3). The results of the evaluation of DNA isolation using a spectrophotometer at a wavelength of A260/280 nm showed a ratio of 1.4, 1.8, and 1.7 at P1 and P2, and P3 respectively. The quantity obtained ranged from 210 to 305 ng/µL. The total DNA results obtained were then used for PCR testing of ITS ribosomal DNA fragments using ITS1 and ITS4 primers. Electrophorosis observation of PCR results showed that all samples produced bands with a length of 500 bp. The results of DNA isolation in the P1 method did not show bands on the agarose gel, but could be seen in the PCR product. Methods P2 and P3 showed DNA that had good quality and quality. The P2 and P3 methods use a cell destruction technique with liquid nitrogen and a combination of addition of proteinase K. The obtained protocol is expected to provide fast and good method information in the isolation of total DNA from A. niger .   Keyword : Aspergillus niger , total DNA isolation, ITS1, ITS4